Asymmetric total synthesis of (+)-xestoquinone and (+)-adociaquinones A and B. Issue 13 (25th February 2021) - Lu, Xiao-Long; Qiu, Yuanyou; Yang, Baochao; He, Haibing; Gao, Shuanhu
Abstract : The asymmetric total synthesis of (+)-xestoquinone and (+)-adociaquinones A and B was achieved in 6–7 steps using an easily accessible meso -cyclohexadienone derivative. Abstract : The asymmetric total synthesis of (+)-xestoquinone and (+)-adociaquinones A and B was achieved in 6–7 steps using an easily accessible meso -cyclohexadienone derivative. The [6, 6]-bicyclic decalin B–C ring and the all-carbon quaternary stereocenter at C-6 were prepared via a desymmetric intramolecular Michael reaction with up to 97% ee. The naphthalene diol D–E ring was constructed through a sequence of Ti(Oi-Pr)4 -promoted photoenolization/Diels–Alder, dehydration, and aromatization reactions. This asymmetric strategy provides a scalable route to prepare target molecules and their derivatives for further biological studies.